Protest dialectics : state repression and South Korea's democracy movement, 1970-1979 - Chang, Paul Y. (Stanford University Press, 2015)
1970s South Korea is characterized by many as the ""dark age for democracy."" Most scholarship on South Korea's democracy movement and civil society has focused on the ""student revolution"" in 1960 and the large protest cycles in the 1980s which were followed by Korea's transition to democracy in 1987. But in his groundbreaking work of political and social history of 1970s South Korea, Paul Chang highlights the importance of understanding the emergence and evolution of the democracy movement in this oft-ignored decade. Protest Dialectics journeys back to 1970s South Korea and provides readers